Penguasaan Tanpa Izin atas Aset Lahan Sitaan Kejaksaan: Studi Yuridis terhadap Celah Penegakan Hukum Pidana - Dairi; Rindiani, Anis; Dewi, Virna (Universitas Muhammadiyah Ponorogo, 2025)
Unauthorized possession of land assets seized by the prosecutor’s office constitutes a form of legal violation that has the potential to hinder the enforcement of criminal law. This study aims to analyze the criminal law provisions governing the possession of seized land assets and to identify the obstacles and legal loopholes that arise in its enforcement practices. The research method employed is a normative juridical approach with a focus on the study of positive law. Data collection techniques were carried out through literature study of statutory regulations, legal literature, and relevant court decisions, combined with secondary data in the form of official documents from the prosecutor’s office related to the management of evidence and seized property. Data analysis techniques used normative qualitative analysis, namely by interpreting positive legal norms, linking them with legal doctrines, and comparing their application in judicial practice.The findings of this research indicate that illegal possession of seized assets is regulated in the Indonesian Penal Code (KUHP), Law Number 8 of 1981 concerning the Criminal Procedure Code, as well as the technical regulations of the prosecutor’s office regarding the management of seized property. However, in practice, there are still several challenges, including weak supervision systems, unclear mechanisms for asset safeguarding, and legal loopholes that allow third parties to physically control assets without official procedures. These findings emphasize the need to strengthen technical regulations, improve supervision systems, and enhance coordination among law enforcement agencies to prevent the misuse of seized land assets by the prosecutor’s office.